Sustainable development and tourism - Speier, Jonathan Van (REVISTA ACADÊMICA OBSERVATÓRIO DE INOVAÇÃO DO TURISMO, 2008)
The intent of this study is to investigate the role and responsibility of tourism from the perspective of sustainable development. The objective of the research was to evaluate the extent to which international tourism in developing countries meets dimensions of sustainable development. The goals and processes of development are reviewed as they evolved after the end of World War II along the path to sustainable development.Tourism, as a major development option, has been promoted for its potential to offer a unique combination of features that provide opportunities to meet established sustainable development dimensions. To examine this hypothesis, a theoretical and methodological framework is constructed with five key dimensions arranged to recognize that, for development to be sustainable, it must embrace social and human as well as economic development goals achieved through processes and institutions operating within the context of protecting existing human cultures and natural environments.Extensive data were collected from sixty sample case-studies across twenty-eight destinations to see if there were occasions where indicators from all five key dimensions of sustainable development were successfully applied. No occasions were found where all the dimensions of sustainable development have been successfully addressed as measured by positive indicators taken from the sample-case studies. This suggests that tourism may not be compatible with sustainable development. Future research should investigate whether sample-case studies describing more recent tourism development show a trend of improvement in the movement towards sustainability.